Anaesthetic Management of Parturients With Univentricular Congenital Heart Disease and the Fontan Operation. Issue 3 (September 2017) - Monteiro, R.S.; Dob, D.P.; Cauldwell, M.R.; Gatzoulis, M.A.
Abstract : ( Int J Obstet Anesth . 2016;28:83–91) Over the past few decades, as surgical treatment of congenital heart disease (CHD) has improved, an increasing number of women with CHD are becoming pregnant and obstetric anesthesiologists must be able to manage these women during labor and delivery. One of the newest challenges is that presented by women with a single ventricular circulation that has been palliated with the Fontan operation.